Toward a political economy of government waste first step, definitions. - Stanbury, William; Fred, Thompson (1995)
William Stanbury and Fred Thompson try to get beyond the mantra of waste, fraud, and abuse to deal seriously and constructively with the question of government waste. They provide a logical taxonomy of nine types of waste. To them a large proportion of the waste created by government is not included in the budget. Indeed, efforts to reduce budgetary waste often simply cause is to pop up elsewhere. A better understanding of the nature and varieties of waste is crucial to improving governmental performance and, ultimately, for the common defense, and promoting the general welfare - for present and future generations
Keywords: Waste in government spending - United States; Expenditures, Public - United States